An electromagnetic wearable 3-DoF resonance human body motion energy harvester using ferrofluid as a lubricant - Wu, Shuai; Luk, Patrick Chi-Kwong; Li, Chunfang; Zhao, Xiangyu; Jiao, Zongxia; Shang, Yaoxing (Elsevier, 2017)
Wearable energy harvester offers clean and continuous power for wearable sensors or devices, and plays an important role in a wide range of applications such as the health monitoring and motion track. In this study, we investigate a small electromagnetic resonance wearable kinetic energy harvester. It consists of a permanent magnet (PM) supported by two elastic strings within a rectangular box form a 3-degree-of-freedom (3-DoF) vibrator. Copper windings are attached to the outer surface of the box to generate electrical energy when the PM is forced to vibrate. To minimize any frictional losses, ferrofluid is used such that the poles of PM are cushioned by the ferrofluid, to the effect that the PM will not touch the inner of the box. Simulation results show that the ferrofluid can keep the PM ‘contactless’ from the box even subject to 10 times gravity acceleration. A prototype is built and tested under different loading conditions. Resistance load experimental results indicate the proposed harvester can generate 1.11.1 mW in walking condition and 2.282.28 mW in running condition. An energy storage circuit is employed and the energy storage experimental results show that the average storage power during walking and running conditions are 0.0140.014 mW and 0.1490.149 mW respectively. It is shown that the developed harvester can be readily attached on a shoe to offer continuous power supply for wearable sensors and devices.
Keywords: Energy harvester; Wearable; Electromagnetic; Generator; Ferrofluid